The intention to adopt parcel lockers as a last-mile delivery services in Malaysia - Darren, Peter; Yong, Penny Pei Nee; Quah, Yan Yee; Woo, Yin Lin (2023)
Last-mile delivery serves as the final connection between the upstream supply chain operations and the end consumers, acting as the ultimate link in the supply chain. Research indicates that the logistics sector has experienced significant financial gains as a result of the swift growth of online commerce. Nevertheless, there has been much attention given to the difficulties that accompany the potential benefits of parcel lockers. To overcome the limitations of conventional last-mile logistics in various distribution scenarios and to update the delivery service concept with advanced technology, the implementation of self-collection services is necessary. This research aims to utilize the Technology Acceptance Model and Theory of Planned Behavior to investigate consumers' preferences in adopting parcel locker services. Specifically, the study seeks to identify the patterns and dimensions of consumer preferences, such as convenience, reliability, relative advantage, and complexity. Additionally, the research examines the mediation effect of customers' attitudes towards parcel locker services in determining their intention to adopt this service. The data was gathered via an internet-based questionnaire (Google Forms) from 138 participants situated within Malaysia. The study's hypotheses were tested using the Statistical Package for the Social Sciences (SPSS) version 27.0. This was done through the application of linear regression, multiple regression analysis, and mediation analysis using the PROCESS Macro. The results indicated that consumer preference, including factors such as convenience, reliability, relative benefit, and complexity, had a substantial impact on consumers' sentiments towards parcel locker service. Furthermore, the results indicated that the attitude towards parcel locker service acts as a mediator in the relation between consumer preferences and the intention to utilize parcel locker service. Therefore, this research contributes to the growing body of knowledge on parcel locker services in Malaysia, a topic that is still in its early stages in the country. This enhances the value of the research findings and is highly relevant to bridge the gap in the emerging literature on parcel locker service in Malaysia. Keywords: parcel locker, last mile delivery, consumers, attitude, intention